Tornando-se educador: reflexões sobre aprendizagens numa banda de música militar - Valentim, Hélio Xavier Guimarães (2023)
This dissertation presents a narrative research that investigates the reflections of a musician during his transition to the role of educator in the Banda de Música da Base Aérea de Santa Maria. The objective of the study is to reflect on this transition process, exploring the paths and learning methods that were taught and adopted by the researcher, with the aim of improving their teaching practice. In order to understand the indirect approaches used, a personal diary was kept based on the theories of Zabalza and Hess, which was later transferred to the class diaries. The research focused on the use of these class diaries about clarinet students. In addition, they were asked to write their own diaries, which were intertwined with the teacher's diaries, in order to get a broader view. During the analysis of these diaries, three main dilemmas emerged: the relational-hierarchical dilemma, the dilemma of young people with disabilities and the curricular dilemma. To analyze the work, the Atlas.ti software was used, which allowed the qualitative understanding of the diaries through coding. In all, twenty-three diaries were analyzed. These diaries were relevant so that the author could identify ways to improve his practice and help students to reach an adequate technical level to perform in the Concerto do Aviador, the most important concert of the year. The process described in this dissertation can encourage the reflection of other teachers of instruments and musicians from military bands, as well as contribute to debates in the area of Education and Music Education. During this period, the author faced the challenge of reconciling his role as an educator with his military role, in search of finding his identity as a teacher-researcher.